Pelatihan Pengembangan Keterampilan Guru SMA Melalui Pembuatan Flipbook Sebagai Sumber Belajar Mandiri - Firdiawan Ekaputra; Fuldiaratman Fuldiaratman; Muhammad Rusdi; Fatria Dewi; Roseli Theis (I-Com: Indonesian Community Journal, 2024)
Teachers play an important role in the quality of learning that is carried out. The limited ability of teachers to operate software or flipbook maker platforms makes learning media that is diverse cannot be developed and applied optimally. Therefore, training for SMA Negeri 15 Muaro Jambi teachers in developing skills through making flipbooks is needed. The training was held on July 18, 2024 at SMA Negeri 15 Muaro Jambi which was attended by 18 teachers from all subjects. The methods used in this training include preparation, implementation and evaluation methods. Skill development training activities through making flipbooks as an independent learning resource that have been carried out have an average achievement of 4.48 with a very good category. The training participants were very enthusiastic about the training conducted regarding making flipbooks as an independent learning resource because SMA Negeri 15 Muaro Jambi teachers experienced an increase in adequate technical skills and creativity and innovation in making flipbook teaching materials.